Avaliação do comportamento das elementos Ni, Rb e Se por espectrometria de absorção atômica com forno tubular na chama de aeressol térmico. - Rosini, Fabiana (2006)
In the present work the behavior of the elements Ni, Rb, and Se was evaluated by thermospray flame furnace atomic absorption spectrometry (TS-FF-AAS). The arrangement of the TS-FF-AAS system consisted of a Ni tube located on the burner head of an air / acetylene flame with a ceramic capillary tube connected to it and heated by the flame. The sample was transported towards the capillary heated tube by action of a peristaltic pump, and then transformed in a thermospray that was introduced into the Ni tube. The sensitivity was increased by the complete introduction of the sample in the absorption volume. For all tested elements, the effect of the main parameters on atomization, such as flame composition, observation height, type of carrier stream, flow rate, and sample volume, was investigated. For selenium, the detection limit obtained was 95-fold better than that obtained by FAAS. Notwithstanding, selenium determination was difficult due to the absorption region of this element (λ = 196 nm), that implied in molecular absorption by flame gases and scattering of radiation. Based on prescribed conditions established by a factorial experiment, selenium was determined with accuracy in samples of animal tissues and in two standard reference materials after microwave-assisted digestion using a diluted solution of acid nitric. For Rb, the sensitivity increased 37-fold compared to FAAS, leading to a detection limit of 2.65 µg/L by TS-FF-AAS. On the other hand, Ni is a refractory element and needed special conditions to facilitate the volatilization and atomization processes. Thus, a cloud point extraction procedure was developed. The combination of both TS-FF-AAS and cloud point extraction led to an improvement of 18-fold in detection limit, however Ni determination in biological samples was limited owing to interferences caused by Al(III), Co(II), and Fe(III). These interferences could be solved by adding fluoride to the digests.